Theory and Description in Latin Linguistics : Selected Papers from the 11th International Colloquium on Latin Linguistics - M. Bolkestein; Caroline Kroon; Harm Pinkster; Remmelink; Rodie Risselada (Amsterdam Studies in Classical Philology, 2002)
With contributions by R. Amacker, C. Bodelot, P. Carvalho, W. Dressler, G. Haverlin, R. Maltby